2008
DOI: 10.1093/annonc/mdm439
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of S-1 and cisplatin in patients with metastatic or relapsed biliary tract cancer

Abstract: Background: Optimal chemotherapy for advanced biliary tract cancer (BTC) is yet to be defined. We carried out this study to evaluate the efficacy and toxicity of combination chemotherapy with S-1 and cisplatin in metastatic or relapsed BTC. , and progressive disease in 9 (18%). With a median follow-up of 12.4 months, the median time to progression was 4.8 months (95% CI, 3.3-6.3) and median overall survival was 8.7 months (95% CI, 6.0-11.4). Major toxic effects were grade 3/4 neutropenia (8.9% of all cycles) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…However, no standard chemotherapy regimen for advanced BTC has been established. Several phase II trials with new chemotherapeutic agents, such as gemcitabine (6)(7)(8)(9)(10), capecitabine (11), oxaliplatin (12), or S-1 (13,14) have demonstrated tumor response in ~15-35% of patients treated with single agents, and in 20-40% of patients treated with their combinations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Among them, gemcitabine has shown promising activity against advanced BTC, and has been commonly used for patients with unresectable or recurrent BTC in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…However, no standard chemotherapy regimen for advanced BTC has been established. Several phase II trials with new chemotherapeutic agents, such as gemcitabine (6)(7)(8)(9)(10), capecitabine (11), oxaliplatin (12), or S-1 (13,14) have demonstrated tumor response in ~15-35% of patients treated with single agents, and in 20-40% of patients treated with their combinations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Among them, gemcitabine has shown promising activity against advanced BTC, and has been commonly used for patients with unresectable or recurrent BTC in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized trial showed that patients with advanced BTA who were treated with 5-FU-based palliative chemotherapy had better survival and a better quality of life than patients given the best supportive care alone [1]. Many cytotoxic agents, including 5-FU, cisplatin, gemcitabine, mitomycin C, oxaliplatin and docetaxel, have been tested against BTA, but none was significantly better when given alone or as part of a combination therapy [2,3,4,5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…for 4 weeks in 6-week cycles) achieved a partial response, 47% had stable disease, and the median overall survival (OS) was 8.3 months. Based on these and other studies of S-1, several combination chemotherapies based on S-1 are currently being tested for the treatment of BTA [4]. …”
Section: Introductionmentioning
confidence: 99%
“…A randomized phase III study demonstrated the superiority of GEM and cisplatin combination chemotherapy to single-agent GEM in patients with advanced BTC, which has made this combination chemotherapy an appropriate treatment option in patient with advanced BTC [15]. 5-FU-based chemotherapy, which gave rise to improvement in quality of life and survival, is another treatment option [7,8,9,10,11]. Also, a systematic review of 2,810 patients with advanced BTC demonstrated that a combination regimen was better than single-agent therapy, and a two-drug regimen of 5-FU or GEM plus platinum was better than other combinations [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, palliative chemotherapy agents including 5-FU, gemcitabine (GEM), cisplatin/oxaliplatin, mitomycin-C (MMC), doxorubicin, docetaxel, and irinotecan have been tested with response rates (RRs) ranging from 10–40% [5,6]. The most classic agent, 5-FU, yields overall RRs (ORRs) of 10% as a single agent and 20–40% with combination chemotherapy [7,8,9,10,11]. Also, GEM-based chemotherapy has been introduced as treatment for patients with BTC and has been reported to yield ORRs of 10–35% [12,13,14].…”
Section: Introductionmentioning
confidence: 99%